Salinomycin induces primary chicken cardiomyocytes death via mitochondria mediated apoptosis. (25th February 2018) - Gao, Xiuge; Zheng, Yani; Ruan, Xiangchun; Ji, Hui; Peng, Lin; Guo, Dawei; Jiang, Shanxiang
Abstract: Salinomycin, as a polyether ionophore antibiotic, is extensively used as a feed additive against coccidiosis in poultry and as a growth promoter of ruminants worldwide. Owing to its narrow therapeutic index, numerous intoxication have been reported in target/non-target animals by overdosage, misuse or drug interactions as well as human who consumed salinomycin accidently. Salinomycin-induced cardiotoxicity in chicken and non-target animals is considered as a major contributor to animal death. In the current study, we aim to elucidate the underlying mechanism of its myocardial toxicity using primary chicken myocardial cell as an in vitro model. The results showed that salinomycin altered cellular morphology and induced cell death in a concentration-dependent manner. Salinomycin treatment elevated the permeability of the cell membrane and leaded to the efflux of enzymes, including creatine kinase (CK) and lactate dehydrogenase (LDH). Flow cytometry analysis indicated the number of apoptotic cells increased significantly by salinomycin exposure. Furthermore, caspase-3 and caspase-9 were activated at gene and protein level rather than caspase-8, along with the up-regulation of apoptosis genes Bax, Cytochrome C, Apoptotic peptidase activating factor 1 (Apaf-1) and the down-regulation of Bcl-2. Salinomycin-induced mitochondrial dysfunction was accompanied by the significant decrease of mitochondrial membrane potential (MMP) and the severe ultrastructure damage. In conclusion, these findings suggest that the toxic dose of salinomycin induces severe cardiomyocytes death through mitochondria mediated apoptosis pathway. Highlights: Salinomycin causes primary chicken cardiomyocytes death. The cell death occurs primarily via apoptosis. Salinomycin increases caspase-3 and caspase-9 gene and enzymatic activity. Salinomycin induces disfunction of mitochondria and decline of mitochondrial membrane potential. Mitochondria mediated apoptosis pathway is involved salinomycin-induced cell death.